KARAKTERISTIK PENDERITA GAGAL GINJAL KRONIK YANG DIRAWAT INAP DI RS MARTHA FRISKA MEDAN TAHUN 2011 - herdiani siallagan (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Chronic Renal Failure (CRF) is a condition caused reduction in renal function that is chronically, progressive and quite advanced. Result of the survey Association of Nephrology Indonesia in 2009 prevalence of GGK in Indonesia around 12,5%. The research was done as descriptive study by using case series design. The purpose of research was done to know the characteristic of CRF patients who are hospitalized in RS Martha Friska Medan in 2011. Population and sample are the same 201 CRF patients. Data obtained from medical records. The highest proportion of the patients with CRF is in the age 49-55 years old (24,8%), Male (53,7%), Bataknesse (61,2%), Moslem (48,7%), Academic/ Universities (50,7%), Civil Servants (PNS)/retired (58,2%), come from Medan (62,2%), diseases history of Hipertension (30,2%), Levels of Bood Urea > 100 mg/100 mL (68,9%), Levels of Blood Creatinine > 4 mg/100 mL (77,0%), medical treatment of Medicine + Diet + Hemodialysis (55,2%), Askes (73,6%), Average length of stay 12,2 days (12 days) with clinical recovery out patient 55,7%). There was no difference between average length of stay based on age patients (p =0,259), There was difference between average length of stay based on medical treatment (p = 0,002), There was difference between average length of stay based on condition when go home (p = 0,001). The hospital is expected to completing data patients in card status especially diseases history, Levels of Bood Urea and Levels of Bood Creatinine also give information to patient about CRF medical treatment. Keywords: Chronic Renal Failure (CRF), the characteristic of patients